2000
DOI: 10.1109/9.847738
|View full text |Cite
|
Sign up to set email alerts
|

A new discrete impulse response Gramian and its application to model reduction

Abstract: International audienceSome fundamental properties of an impulse response Gramian for linear, time-invariant, asymptotically stable, discrete single-input-single-output (SISO) systems are derived. This Gramian is system invariant and can be found by solving a Lyapunov equation. The connection with standard controllability, observability, and cross Gramians is proven. The significance of these results in model-order reduction is highlighted with an efficient procedure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…To illustrate the method two examples are presented. First, we have considered the seventh-order transfer function of a supersonic jet engine inlet [37][38] ( ) The value 24 . 0 = λ for the Laguerre parameter has been obtained using the suboptimal method described in [27,30].…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate the method two examples are presented. First, we have considered the seventh-order transfer function of a supersonic jet engine inlet [37][38] ( ) The value 24 . 0 = λ for the Laguerre parameter has been obtained using the suboptimal method described in [27,30].…”
Section: Examplesmentioning
confidence: 99%
“…Response Gramian (GIRG5 see [38]) and Laguerre-SVD (LSVD5 see [40]). The latter was implemented using the same Laguerre parameter as LG5 ( 24 .…”
Section: Examplesmentioning
confidence: 99%
“…In model reduction of discrete-time systems, impulse response Gramians are very important, and they can be used to derive the reduced-order model. In [13] and [1], the concepts of weighted and generalized impulse response Gramians were respectively proposed, and it was shown that these Gramians can be obtained by solving the corresponding discrete Lyapunov matrix equations. In addition, the discrete Lyapunov matrix equation can also be used to analyze the stability of periodic discrete-time systems [12].…”
mentioning
confidence: 99%
“…modeling turbomachinery, supersonic flows in jet engine inlets [4], [9], [37], [49], [115]- [117], efficient modeling of biological systems [50], [51], [120], rapid thermal processing [2], problems in chemical [61] or mechanical [59] engineering.…”
Section: Motivationmentioning
confidence: 99%
“…Due to this fast growing complexity, applicability of TBR methods for large-scale systems is limited. In order to overcome this difficulty methods based on approximate Grammian computation have been developed [4], [10], [64], [65], [71], [87], [99], [105], [121].…”
Section: Previous Work On Model Order Reductionmentioning
confidence: 99%